Improved pentamethine cyanine nanosensors for optoacoustic imaging of pancreatic cancer - Matthew D. Laramie (Nature Portfolio, 2021)
Abstract Optoacoustic imaging is a new biomedical imaging technology with clear benefits over traditional optical imaging and ultrasound. While the imaging technology has improved since its initial development, the creation of dedicated contrast agents for optoacoustic imaging has been stagnant. Current exploration of contrast agents has been limited to standard commercial dyes that have already been established in optical imaging applications. While some of these compounds have demonstrated utility in optoacoustic imaging, they are far from optimal and there is a need for contrast agents with tailored optoacoustic properties. The synthesis, encapsulation within tumor targeting silica nanoparticles and applications in in vivo tumor imaging of optoacoustic contrast agents are reported.